The art of problem solving in organic chemistry - Alonso, Miguel E. 4 0 16; 5 (New York : John Wiley & Sons, 1987)
Explains how to solve problems in organic chemistry with 56 problems and discussion on how to solve each problem.
A Wiley-Interscience publication.
Includes bibliographical references and indexes.
Adult;Adult
Keywords: 2 -- 0; 6; Chemistry, Organic.;Problem solving.;Organic chemistry.;Problem solving; 20; 2